2018
DOI: 10.1016/j.atherosclerosis.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in hyperlipidaemia patients based on administrative claim databases in Japan

Abstract: Most common prescriptions were moderate statins in UT patients and combination therapy in PT patients. The high discontinuation rate of HLD therapy in UT patients warrants further investigation and identification of methods to encourage and support long-term persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…However, a meta-analysis of population cohorts by KDIGO showed a linear relationship between lower eGFR level and risk of CV mortality; namely CKD patients with an eGFR level less than 15 mL/min/1.73 m 2 had the highest risk of CV mortality (HR, 3.14; 95% CI, 2.39-4.13) compared to eGFR 95 mL/min/1.73 m 2 (14). One possible explanation of the difference between previous studies and the present one is that patients who have any potential risks of CV diseases with a lower eGFR level might be transferred to other hospitals for dialysis treatment, and therefore information on events, particularly among the stratified group of eGFR < 15 mL/min/1.73 m 2 , could not be captured due to the characteristics of the MDV database (15).…”
Section: Discussioncontrasting
confidence: 58%
“…However, a meta-analysis of population cohorts by KDIGO showed a linear relationship between lower eGFR level and risk of CV mortality; namely CKD patients with an eGFR level less than 15 mL/min/1.73 m 2 had the highest risk of CV mortality (HR, 3.14; 95% CI, 2.39-4.13) compared to eGFR 95 mL/min/1.73 m 2 (14). One possible explanation of the difference between previous studies and the present one is that patients who have any potential risks of CV diseases with a lower eGFR level might be transferred to other hospitals for dialysis treatment, and therefore information on events, particularly among the stratified group of eGFR < 15 mL/min/1.73 m 2 , could not be captured due to the characteristics of the MDV database (15).…”
Section: Discussioncontrasting
confidence: 58%
“…This study is a retrospective observational analysis using de-identified, individual-level data obtained from the health claims database of the Japan Medical Data Center (JMDC), Tokyo, between 2005 and 2017. [11][12][13][14][15] This database contains medical claims data provided by multiple health insurance services for employees and their family members. Included are patient demographics, diagnosis codes recorded as standardized local codes of diseases defined by the Medical Information System Development Center mapped to the International Classification of Diseases (ICD)-10 codes, prescriptions, medical procedures and examinations.…”
Section: Study Design and Source Of Datamentioning
confidence: 99%
“…Another reason would be statin intolerance. A recent report 15) analyzed administrative claim databases in Japan, and the results showed that more than 20% of patients discontinued their medication for dyslipidemia within one year after the initiation of medication; for high-dose statin therapy, that amount exceeded 60%. Statin intolerance, including the nocebo effect 16) , might somehow have contributed to this discontinuation.…”
Section: Discussionmentioning
confidence: 99%